2008
DOI: 10.1093/hmg/ddn211
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory changes in the ubiquitin-proteasome system, brain-derived neurotrophic factor and mitochondrial complex II/III in YAC72 and R6/2 transgenic mice partially model Huntington's disease patients

Abstract: Intraneuronal protein aggregates of the mutated huntingtin in Huntington's disease (HD) brains suggest an overload and/or dysfunction of the ubiquitin-proteasome system (UPS). There is a general inhibition of the UPS in many brain regions (cerebellum, cortex, substantia nigra and caudate-putamen) and skin fibroblasts from HD patients. In the current experiment, the widely used mutant huntingtin-exon 1 CAG repeat HD transgenic mice model (R6/2) (with 144 CAG repeat and exon 1) during late-stage pathology, had i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 56 publications
2
23
1
Order By: Relevance
“…At late stage of disease (12 months), we found that both striatal and cortical mBDNF levels are markedly reduced, which correlate with overt onset of behavioral and cognitive symptoms. The age- and region-dependent reduction of mBDNF is consistent with progressive loss of bdnf gene transcription (Gines et al, 2003; Zuccato et al, 2005; Seo et al, 2008; Bobrowska et al, 2011; Sontag et al, 2012; Plotkin et al, 2014). …”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…At late stage of disease (12 months), we found that both striatal and cortical mBDNF levels are markedly reduced, which correlate with overt onset of behavioral and cognitive symptoms. The age- and region-dependent reduction of mBDNF is consistent with progressive loss of bdnf gene transcription (Gines et al, 2003; Zuccato et al, 2005; Seo et al, 2008; Bobrowska et al, 2011; Sontag et al, 2012; Plotkin et al, 2014). …”
Section: Discussionmentioning
confidence: 71%
“…Although reduced trophic support of BDNF has been proposed as an underlying mechanism in HD pathogenesis, prior studies in HD mouse models showed conflicting results regarding the levels of BDNF in the cortex and the striatum (Gines et al, 2003; Seo et al, 2008; Bobrowska et al, 2011; Sontag et al, 2012; Plotkin et al, 2014). Moreover, the ratio of proBDNF to mBDNF in the striatum of wild type and HD mice remains unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that striatal levels of mature BDNF were also reduced in YAC128 mice. However, ELISA assays show normal striatal levels of BDNF in R6/1 mice (Canals et al, 2004; Pang et al, 2006) and increased striatal levels of BDNF in YAC72 mice (Seo et al, 2008). As ELISA assays detect both mature BDNF and proBDNF, this discrepancy suggests that processing of proBDNF may be impaired in the striatum, leading to accumulation of proBDNF in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Western blot data, proteasome activity assays on striatal homogenates showed a trend of decreased caspase-like activity only after 1 week of transgene expression (15.6 Ϯ 18.8% decrease, p ϭ 0.54). In the case of chymotrypsin activity, the opposite result (a trend of increased activity) was observed (data not shown), which can be easily explained by the fact that a selective upregulation of this activity is well established in N-mutHtt mouse models (Diaz-Hernandez et al, 2003;Seo et al, 2004;Bett et al, 2006;Seo et al, 2008). …”
Section: Transient Accumulation Ubmentioning
confidence: 92%